Blood loss and transfusion rates associated with transcatheter aortic valve replacement: Recommendations for patients who refuse blood transfusion. Issue 6 (31st January 2014) - Binder, Ronald K.; Barbanti, Marco; Ye, Jian; Toggweiler, Stefan; Tan, John; Freeman, Melanie; Cheung, Anson; Wood, David A.; Webb, John G.
<x xml:space="preserve">Abstract</x> Background Transcatheter aortic valve replacement (TAVR) is less invasive than surgical aortic valve replacement and may be preferred for patients who refuse blood transfusions. Objectives Our study sought to define transfusion rates in TAVR, identify predictors and develop recommendations for patients who refuse transfusions. Methods A large cohort of consecutive patients undergoing TAVR was prospectively studied. Blood loss and transfusion rates were observed in patients undergoing transfemoral (TF‐TAVR) and transapical TAVR (TA‐TAVR). Predictors for transfusion were investigated in a multivariate model. Results Of 373 consecutive patients, 270 underwent TF‐TAVR and 103 TA‐TAVR. Transfusion rates were significantly lower in TF‐TAVR than TA‐TAVR (11.1 vs 41.7%; P < 0.001). In patients who did not receive transfusions, blood loss was significantly lower in TF‐TAVR than TA‐TAVR (23.6 ± 12.2 g/l vs 28.9 ± 13.7 g/l; P = 0.004), but did not differ in transfused patients (36.9 ± 12.9 g/l vs 33.4 ± 21.2 g/l; P = 0.428). Predictors for transfusions were low baseline hemoglobin, female sex, low body weight and decreased renal function. In seven Jehovah's Witness patients, who refused transfusions, no vascular complications occurred and clinical outcome was excellent. Conclusion In patients, who refuse transfusions, TAVR may be performed with good clinical outcomes provided a high baseline hemoglobin level, careful management of the access site and strict measurements to reduce blood loss. TF‐TAVR is associated with less blood loss and a lower rate of transfusions than TA‐TAVR, and may be the preferred option for patients, who refuse transfusions. © 2014 Wiley Periodicals, Inc.